Incidence of hypernatremia in dogs treated with multi-dose activated charcoal for acute toxicant ingestion: multi-center retrospective study (2018–2023) - Gabriel, Leah; Walton, Rebecca A. L.; Young, Timothy; Cai, Jiazhang; Mochel, Jonathan P.; Peterson, Katherine (Frontiers in Veterinary Science, 2025)
ObjectiveTo retrospectively evaluate the incidence of hypernatremia in dogs administered multi-dose activated charcoal (MDAC) for acute toxicant ingestion.MethodsRetrospective study between the years 2018–2023. Ninety-seven dogs evaluated by a university teaching hospital and private practice emergency hospital treated for acute toxicant ingestion with multi-dose of activated charcoal, with or without sorbitol.ResultsNinety-seven dogs were included. The median serum sodium concentration (Na) on presentation was 146.7 mEq/L (range 139–154.7 mEq/L), at 6–12 h 145.6 mEq/L (range 137–152.3 mEq/L), at 12–24 h 144 mEq/L (range 132.5–155) and at 24–48 h 144 mEq/L (range 134–150 mEq/L). Twenty-one dogs (21.6%) received 2 doses of AC, 37 dogs (38.1%) received 3 doses, 25 dogs (25.8%) received 4 doses, 3 dogs (3%) received 5 doses, and 11 dogs (11.3%) received 6 doses. There was no statistically significant difference in the type of toxicant ingested and changes in serum Na. No dog had a serum Na above 155 mEq/L. In dogs that received 2 doses of AC, there was no significant difference in serum Na at any time point. In dogs that received 3 total doses of AC there was a statistically significant decrease in serum Na at 12–24 and 24–48 h (p < 0.01). In dogs that had a total of 4 doses of AC, there was a statistically significant decrease in Na was noted at 12–24 h and 24–48 h (p < 0.01). For dogs that received 5 or 6 doses of AC, there was a significant decrease in serum Na at 6–12 h (p = 0.02). All dogs were hospitalized and 95 (98%) received intravenous fluids. The fluid rate and type were not significantly associated with changes in serum Na. Packed cell volume, total plasma protein, blood glucose and lactate on presentation were not significantly associated with change in serum Na at any time frame. All dogs survived to discharge.ConclusionIn this study, no dog receiving multi-dose activated charcoal developed hypernatremia and serum Na tended to decrease over time, which is unlikely to be clinically significant.